Individual Differences in Subconscious Motor Control Predicted by GABA Concentration in SMA - Frederic Boy (Current Biology, 2010)
Subliminal visual stimuli affect motor planning [1], but the size of such effects differs greatly between individuals [2, 3]. Here, we investigated whether such variation may be related to neurochemical differences between people. Cortical responsiveness is expected to be lower under the influence of more of the main inhibitory neurotransmitter, GABA [4]. Thus, we hypothesized that, if an individual has more GABA in the supplementary motor area (SMA)—a region previously associated with automatic motor control [5]—this would result in smaller subliminal effects. We measured the reversed masked prime—or negative compat- ibility—effect, and found that it correlated strongly with GABA concentration, measured with magnetic resonance spectroscopy. This occurred specifically in the SMA region, and not in other regions from which spectroscopy measure- ments were taken. We replicated these results in an inde- pendent cohort: more GABA in the SMA region is reliably associated with smaller effect size. These findings suggest that, across individuals, the responsiveness of subcon- scious motor mechanisms is related to GABA concentration in the SMA.